Minimally invasive video-assisted sphincter-sparing treatment of complex rectal fistulas using the VAAFT technique - A. O. Atroschenko (Тазовая хирургия и онкология, 2020)
Background. Video-assisted anal fistula treatment (VAAFT) is a new minimally invasive sphincter-sparing technology.Objective: to describe technical characteristics of VAAFT and evaluate short-term outcomes.Materials and methods. We used a specialized surgical video system (VAAFT®; Karl Storz) for the treatment of complex high rectal fistulas. This technology allows a surgeon to use a special fistuloscope to perform visual examination of the fistula, find its internal opening, and detect secondary fistula passages and inflows. In addition to visual inspection, it is possible to simultaneously conduct a cytological brush through the working channel of the endoscope in order to clear the fistula from detritus and desquamate lining mucosa, and then perform fistula ablation using a monopolar electrode. The internal opening of the fistula can be either closed by a flap or sutured using a linear stapling device or closed using an endoscopic clip with additional sealing of the suture line with biological glue.Results. Between September 2017 and August 2019, a total of 112 patients underwent VAAFT® surgeries. Ninety-three patients (83 %) were followed up for 6 months postoperatively. We observed no significant complications during the follow-up period. The majority of study participants (85 %) did not experience severe pain (>2–4 points on a visual-analog scale) in the early postoperative period. Primary healing was achieved in 98 patients (87.5 %) within 2–3 months. Eighty-nine individuals (79.5 %) were followed up for more than 1 year. Rectal fistula healing within 1 year after VAAFT® surgery was observed in 82 % of patients.Conclusions. The main advantage of the VAAFT® technique is the combination of the diagnostic stage for fistula visualization and identification of the internal opening with the possibility of simultaneous surgical treatment.